Glucocorticoid hormones and energy homeostasis - Guia, Roldan M. de; Rose, Adam J.; Herzig, Stephan (Hormone molecular biology and clinical investigation, 2014)
Abstract Glucocorticoids (GC) and their cognate intracellular receptor, the glucocorticoid receptor (GR), have been characterised as critical checkpoints in the endocrine control of energy homeostasis in mammals. Indeed, aberrant GC action has been linked to a variety of severe metabolic diseases, including obesity, insulin resistance and type 2 diabetes. As a steroid-binding member of the nuclear receptor superfamily of transcription factors, the GR translocates into the cell nucleus upon GC binding where it serves as a transcriptional regulator of distinct GC-responsive target genes that are - in many cases - associated with glucose and lipid regulatory pathways and thereby intricately control both physiological and pathophysiological systemic energy homeostasis. Here, we summarize the current knowledge of GC/GR function in energy metabolism and systemic metabolic dysfunction, particularly focusing on glucose and lipid metabolism.
Gesehen am 30.11.2020